Terapia comunitária integrativa: impacto na vida de mulheres, mães de autistas (história oral temática) - Sousa, Brena Stefani Meira Acioly de (2018)
It is a qualitative research, in which the Thematic Oral History was used to obtain the main sources. The present study had the following objectives: To know the life history of women, mothers of autistics, their experiences of care, highlighting the obstacles / difficulties, and possible transformations when participating in the wheels of Integrative Community Therapy; Describe the main obstacles experienced by these women in caring for their children, and not caring for oneself; To highlight the transformations that occurred in the lives of these women after becoming participants of the TCI wheels; To identify whether women, mothers of autistic children, feel included and contemplated in the network of mental health care in the State of Paraíba. The study site was the public bandstand of the city of Cabedelo - Paraíba, where the wheels of integrative community therapy took place with women, mothers of autistic children. The empirical material was produced from a semi-structured interview with participants of at least 24 therapy wheels. In all, five collaborators were chosen, and the product of the material was discussed based on Minayo's thematic analysis methodology, from which four major thematic axes emerged: The loss of the idealized child and the Maria Syndrome; They are autistic mothers, their pains and their loves; Women's Therapy; The care network: Where are the mothers of autistic children? This research obeyed the ethical and legal aspects of the norms and guidelines set forth in resolution 466/2012 of the National Health Council, which regulates researches with human beings, attributed and conferred by Law No. 8,080, dated September 19, 1990, and by Law No. 8,142 of December 28, 1990. The archiving of collected material will be under the tutelage of the Graduate Program in Nursing of the Federal University of Paraíba (PPGEnf / UFPB). The discourse of the collaborators revealed that the mothers who care for their autistic children, although affectionate, bring in their speeches and altruistic attitudes, the appeal of those who suffer. This suffering has a social dimension, in that in this web are placed political, cultural, gender and community issues and reverberates in the physical and psychological field. They also revealed that community-based integrative therapies brought about changes, the main one being the triggering of a self-reflexive process about their roles. Although they did not feel they were covered by the state's mental health care network, these women were able to rebuild and take care of themselves. In this context, it can be seen that the TCI welcomed these mothers and stories of suffering and struggle allowing a contemplation of their true roles, Women.